Molecular docking based approach for the design of novel luteolin analogues as ppar gamma inhibitors - VASUDEV PAI; ARAVINDA PAI (International Journal of Pharma and Bio Sciences, 2016)
Metabolic disorder characterized by hyperglycemia and glycosuria with disturbed carbohydrate metabolism or metabolism of fats and amino acid resulting from defects in insulin secretion or insulin sensitivity leads to a condition called diabetes mellitus. In recent years, the peroxisome proliferator-activated receptor γ (PPARγ) has become a validated target for the treatment of type II diabetes and other related conditions as evidenced in vast number of literatures. The literature search also gave us a hint that flavonoids like luteolin are also the inhibitors of PPAR gamma without producing adipocyte differentiation unlike thiazolidinedione. With this background, it was thought to design novel luteolin analogues against PPAR gamma and to explore their binding affinities and to compare them with standard luteolin. The designed analogues will be a milestone in the discovery of novel antidiabetic agents which would also be free from the side effects of thiazolidinones.